for the function, h(x) = bx - 22, b is a constant and h(-5) = -7. Find the value of h(5)
h(-5) = -5b - 22
Since we're given h(-5) = -7, we have:
-5b - 22 = -7
Typing this equation into our search engine, we get:
b = -3
So our h(x) equation is now:
h(x) = -3x - 22
The problem asks for h(5):
h(5) = -3(5) - 22
h(5) = 15 - 22
h(5) = -37
h(-5) = -5b - 22
Since we're given h(-5) = -7, we have:
-5b - 22 = -7
Typing this equation into our search engine, we get:
b = -3
So our h(x) equation is now:
h(x) = -3x - 22
The problem asks for h(5):
h(5) = -3(5) - 22
h(5) = 15 - 22
h(5) = -37